Tourism Satisfaction Analysis in Bali’s Glamping as Tourism Packages: Women Solo Traveller’s Perspective - Ni Desak Made Santi Diwyarthi; Nyoman Reni Ariasri; Made Darmiati (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
Bali continues to diversify its tourism offerings, glamping—glamorous camping that blends nature with modern comfort—has emerged as a favored choice among women solo travelers. This study investigates the satisfaction levels of women traveling alone who participated in glamping experiences in Candi Kuning Village, Tabanan, Bali. Using a mixed-method approach, data were gathered through questionnaires from 30 respondents and in-depth interviews with 10 participants. Quantitative analysis was conducted using the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA), while qualitative insights were explored through thematic analysis. The CSI score of 83.5% places traveler satisfaction in the “very satisfied” category. IPA results highlighted that the most valued aspects were interpersonal interactions, cultural storytelling, and the perceived safety and empathy of service providers. Conversely, operational elements such as food service procedures and pricing transparency were deemed less critical. Notably, environmental cleanliness—while highly rated—was considered excessive by some travelers who preferred deeper cultural authenticity. This study concludes that women solo travelers seek personalized, emotionally engaging, and culturally immersive experiences over standardized service components. Recommendations are offered to optimize glamping tourism packages through flexible, co-created, and transformative experiences that align with the evolving preferences of this demographic.